Advances in immunotherapy for Alzheimer's Disease 2020-2023 – a literature review - Michalak, Mateusz; Kucharczyk, Piotr; Parzęcka, Karolina; Symulewicz, Michał; Domaradzki, Olaf; Zań, Weronika; Kusy, Bartłomiej; Stolińska, Marta; Szczepanik, Kinga (Journal of Education, Health and Sport, 2025)
Introduction: Alzheimer's disease is an increasing problem in aging European societies. Almost 9 million Europeans already suffer from this disease. The aim of this article is to provide an objective overview of new immunotherapy and vaccination methods among published research results from 2020-2023. Materials and methods: This paper is based on medical articles collected in the PubMed database from 2020-2023. The research was conducted by analyzing keywords such as: "Alzheimer Disease," "Immunotherapy"/"Vaccination" and "Treatment." Results: Recent years have seen a large increase in research directed at AD immunotherapy. Among these, those on aducanumab, donanemab and lecanemab are particularly noteworthy. Lecanemab and aducanumab are already registered in the US, among others. More studies should be expected to try to solve the problems of qualifying patients into the appropriate groups or increasing the number of variables in ongoing trials. This will allow an even more reliable evaluation of the molecules under study and, consequently, further registrations of medicinal products.